2016
DOI: 10.1097/rct.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Fat Embolism Syndrome

Abstract: In FE syndrome, pulmonary CT findings are ground-glass opacities and dependent consolidations, associated with other variably overlapping signs, such as lobular opacities, random nodules, septal thickening, and bronchial wall thickening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…Chest radiography is normal in majority of patients. CT thorax may show bilateral ground glass opacities which are well demarcated 11, 17. CT scan chest of our patient has already been described above.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Chest radiography is normal in majority of patients. CT thorax may show bilateral ground glass opacities which are well demarcated 11, 17. CT scan chest of our patient has already been described above.…”
Section: Discussionsupporting
confidence: 72%
“…CT thorax may show bilateral ground glass opacities which are well demarcated. 11 , 17 CT scan chest of our patient has already been described above. Treatment is mainly supportive.…”
Section: Discussionmentioning
confidence: 59%
“…The amount of lung showing GGO correlates with disease severity (30). Airspace consolidation is distributed in a gravity-dependent distribution similar to ARDS (31). It is important to note that early cases of FES might have a virtually negative assessment on CT (31).…”
Section: Pulmonary Edema Resulting From Various Conditions/diseasesmentioning
confidence: 99%
“…Airspace consolidation is distributed in a gravity-dependent distribution similar to ARDS (31). It is important to note that early cases of FES might have a virtually negative assessment on CT (31). Relevant imaging findings peak approximately 48 h after the post-traumatic release of fat.…”
Section: Pulmonary Edema Resulting From Various Conditions/diseasesmentioning
confidence: 99%
“…Piolanti et al. demonstrated that plain CT findings are not specific for diagnosing FES 6 . Furthermore, since FES is formed from small fat particles mainly distributed in the periphery, 7 abnormal findings on CTPA are very rare 8 .…”
Section: Discussionmentioning
confidence: 99%